A liberdade religiosa e o sábado como dia sagrado para os Adventistas do Sétimo Dia - Nascimento, Marjorie Maria da Silva (2018)
The main objective of this research was to analyze whether conscientious objection as a constitutional guarantee can bring effectiveness to the religious freedom of Seventh-day Adventists in the custody of the Sabbath, a sacred day dedicated exclusively to religious worship and spiritual activities. In order to reach this conclusion, it was tried to show the importance of religious freedom, in its aspects, freedom of conscience, freedom of worship, freedom of belief and the excuse of conscience. As a specific objective, the aim was to show the role of the secular State in the concreteness of religious freedom in a democratic country that respects fundamental human rights, especially freedom of belief and worship. The social relevance of research is justified insofar as many Seventh-day Adventists are deprived of their rights, when they cannot participate in public selections and contests, attend classes on Sabbath days, work on that day, since their conscience and their beliefs do not allow these activities to be performed during the holy hours of the Sabbath. The relevance of the research is made by pointing out solutions so that the sacred day of the Adventists takes effect before the difficulties in the Sabbath keeping and, in addition, contribute to the discussion on the subject before the oscillations in the decisions of the courts. For this purpose, bibliographical references of authors versed in this area were used to formulate conclusions and reach the objectives outlined. As a conclusion, it was pointed out that the solution for Adventists to enjoy the right to keep the Sabbath, without depriving themselves of the right to education, to participate in competitions is the granting of alternative services, as sanctioned by art. 5, VII of CF / 88